Perkembangan Museum Sejarah Alquran di Sumatera Utara: Kontribusi Terhadap Pelestarian Warisan Sejarah Islam - Parinduri, Nurul Aulia; Siregar, Yusra Dewi; Naldo, Jufri (Local History & Heritage, 2024)
This study explores the development of the Alquran History Museum in North Sumatra and its contribution to preserving the Islamic historical heritage in the region. The central research question focuses on how the museum sustains its operations and relevance in safeguarding Islamic historical values. A qualitative research approach was employed, utilizing data collection techniques such as in-depth interviews, observations, and document analysis. The findings reveal that the museum has made significant progress in the management of collections and public services, although it faces challenges related to limited funding and reliance on government support. Despite these obstacles, the museum plays a crucial role as an institution that preserves and promotes Islamic historical heritage in North Sumatra. In conclusion, the museum is a valuable cultural asset with significant potential to further evolve as a center for Islamic history education in the region.